Elastoplastic frictional collisions with Collisional-SPH. (April 2022) - Vyas, Dhairya R.; Cummins, Sharen J.; Delaney, Gary W.; Rudman, Murray; Cleary, Paul W.; Khakhar, Devang V.
Abstract: Elastoplastic frictional collisions are encountered in a wide range of applications. For modelling these, inclusion of both the elastoplastic material response and history-dependent collisional forces is essential. The Collisional-SPH method, originally developed for elastic collisions, incorporates frictional collision forces into SPH and accounts for their history-dependence. In this paper, CSPH is extended to model elastoplastic collisions by incorporating an elastoplastic material model. A thorough validation of this elastoplastic CSPH method is presented. CSPH is then used to analyse the influence of deformation on history-dependent collision forces. It is found that the elastoplastic deformation and the resulting shape change of the substrate alter the contact-zone mechanics by influencing the local tangential force distribution. These effects become more pronounced with increasing deformation. Highlights: Collisional-SPH is extended to model elastoplastic frictional collisions. Predicted substrate deformation and rebound kinematics are validated with several experiments. The pure sliding limit is found to increase with substrate deformation. Substrate deformation also leads to a reduced rebound spin magnitude as the impact angle increases.